2022
DOI: 10.1063/5.0083897
|View full text |Cite
|
Sign up to set email alerts
|

Progress toward picosecond on-chip magnetic memory

Abstract: We offer a perspective on the prospects of ultrafast spintronics and opto-magnetism as a pathway to high-performance, energy-efficient, and non-volatile embedded memory in digital integrated circuit applications. Conventional spintronic devices, such as spin-transfer-torque magnetic-resistive random-access memory (STT-MRAM) and spin–orbit torque MRAM, are promising due to their non-volatility, energy-efficiency, and high endurance. STT-MRAMs are now entering into the commercial market; however, they are limite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 115 publications
(181 reference statements)
0
11
0
Order By: Relevance
“…In recent years, spintronics (1-3) has gained considerable attention and shows great promise for low-power, nonvolatile memory technology. While magnetic memory devices based on spin-transfer torque (STT) have already been introduced to the market (4)(5)(6), they still present some challenges such as device lifetime (10 10 write cycles limited by tunnel barrier breakdown), relatively slow switching speed and the write error rate (due to the stochastic thermal fluctuation induced switching initiation), which are affecting its performance compared to the state-of-the-art semiconductor memory devices (3,4). Spin-orbit torque (SOT)-based devices, on the other hand, are expected to largely overcome these problems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, spintronics (1-3) has gained considerable attention and shows great promise for low-power, nonvolatile memory technology. While magnetic memory devices based on spin-transfer torque (STT) have already been introduced to the market (4)(5)(6), they still present some challenges such as device lifetime (10 10 write cycles limited by tunnel barrier breakdown), relatively slow switching speed and the write error rate (due to the stochastic thermal fluctuation induced switching initiation), which are affecting its performance compared to the state-of-the-art semiconductor memory devices (3,4). Spin-orbit torque (SOT)-based devices, on the other hand, are expected to largely overcome these problems.…”
Section: Introductionmentioning
confidence: 99%
“…2 Department of Electrical Engineering and Computer Sciences, University of California, Berkeley, CA 94720, USA. 3 Department of Physics and Nanotechnology, SRM Institute of Science and Technology, Kattankulathur-603 203, Tamil Nadu, India. 4 Department of Engineering, University of San Francisco, San Francisco CA 94117, USA.…”
Section: Introductionmentioning
confidence: 99%
“…In 2012, it was even established that the circular polarization could be disregarded completely, leading to the process of helicity-independent all-optical switching [9,10]. These seemingly paradoxical results -disproving the long-held notion that magnetic fields must be at least somewhat involved to reverse magnetization -has since triggered intense research efforts [11] aimed at engineering ever-faster switching capabilities under non-equilibrium conditions in a wide array of materials, ultimately targeting practical application within ultrafast memory technologies [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that single pulse all-optical switching (AOS) of the magnetization in 3d-4f ferrimagnets is the fastest and one of the least dissipative ways of magnetization switching [1][2][3][4][5] . This mechanism not only offers means for ultrafast memory operations, but also gives rise to integration between integrated photonics and spintronics 2,6 , in which the 3d-4f ferrimagnets should prevail 7 .…”
mentioning
confidence: 99%
“…It is well-known that single pulse all-optical switching (AOS) of the magnetization in 3d-4f ferrimagnets is the fastest and one of the least dissipative ways of magnetization switching [1][2][3][4][5] . This mechanism not only offers means for ultrafast memory operations, but also gives rise to integration between integrated photonics and spintronics 2,6 , in which the 3d-4f ferrimagnets should prevail 7 . Initially observed in a 3d-4f alloy systems 4 , recently, it was found that the Co/Gd bilayer 8,9 based synthetic ferrimagnets exhibit likewise this ultrafast (ps switching time scale 10,11 ) single pulse AOS process.…”
mentioning
confidence: 99%